Prevalence of sleep bruxism in children: A systematic review - Machado,Eduardo (2014)
INTRODUCTION: Prevalence of sleep bruxism (SB) in children is subject to discussions in the literature.OBJECTIVE: This study is a systematic literature review aiming to critically assess the prevalence of SB in children.METHODS: Survey using the following research databases: MEDLINE, Cochrane, EMBASE, PubMed, Lilacs and BBO, from January 2000 to February 2013, focusing on studies specifically assessing the prevalence of SB in children.RESULTS: After applying the inclusion criteria, four studies were retrieved. Among the selected articles, the prevalence rates of SB ranged from 5.9% to 49.6%, and these variations showed possible associations with the diagnostic criteria used for SB.CONCLUSION: There is a small number of studies with the primary objective of assessing SB in children. Additionally, there was a wide variation in the prevalence of SB in children. Thus, further, evidence-based studies with standardized and validated diagnostic criteria are necessary to assess the prevalence of SB in children more accurately.